In operando Synchrotron XRD/XAS Investigation of Sodium Insertion into the Prussian Blue Analogue Cathode Material Na1.32Mn[Fe(CN)6]0.83·z H2O. (10th May 2016) - Sottmann, Jonas; Bernal, Fabian L.M.; Yusenko, Kirill V.; Herrmann, Matthias; Emerich, Hermann; Wragg, David S.; Margadonna, Serena
Graphical abstract: Abstract: Prussian Blue Analogues (PBAs) with general formula Na x MA [MB (CN)6 ] y · z H2 O (MA, MB  = transition metal) are promising low cost, high rate and high capacity cathodes for sodium ion battery (SIB) technology. Here, we have studied the PBA Na1.32 Mn[Fe(CN)6 ]0.83 · z H2 O ( z  = 3.0 and 2.2) with varying structural modifications (monoclinic and cubic) using in operando quasi-simultaneous X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS). We observed a series of reversible structural phase transitions which accompany Na insertion/extraction during electrochemical cycling. The samples show pronounced differences in their galvanostatic charge and discharge profiles which could be linked to structural and electronic response. Different desodiation and sodiation mechanisms were identified. The influence of [Fe(CN)6 ] vacancies and water content on the electrochemical performance was investigated.